Pengaruh Penggunaan Alat Peraga Terhadap Motivasi Belajar Tematik Siswa Kelas V - Firmansyah, Muhamad Taufiq; Khusniati, Yuni (Tarsib: Jurnal Program Studi PGMI, 2023)
Abstract: The use of teaching aids is one way that teachers can use to increase students' thematic learning motivation. The success of using teaching aids is determined by whether or not students are motivated by following a learning process. teaching aids are tools used to assist the teaching and learning process so that the communication process runs better and is communicative. While motivation is an impulse that arises in each individual to do something. the researchers wanted to conduct a study with a focus on the effect of the use of teaching aids on the thematic learning motivation of fifth grade students at MI. Raden Rahmat Kauman 2021/2022, which includes: 1) teaching aids in MI. Raden Rahmat 2) the application of teaching aids in increasing the thematic learning motivation of fifth grade students 3) the effect of using teaching aids on the thematic learning motivation of fifth grade students at MI. raden of the mercy of the people. The type of research used is field research with a correlational approach. data obtained through observation, questionnaires, and interviews. analysis is done through; normality test, data homogeneity test, data linearity test, linear regression equation, correlation coefficient, and coefficient of determination. The results of this study are at a significant level of 5% with N = 14 is 0.5314. it is known that F arithmetic is greater than f table (0.7619 < 0.5324). based on the calculation results also show that between the variables of the use of teaching aids (variable X) on the thematic learning motivation of class V students (variable y) there is an effect of 51.4%. Thus it can be concluded that there is an effect of using teaching aids on the thematic learning motivation of fifth grade students at MI. Raden Rahmat Kauman.